2010
DOI: 10.3354/meps08638
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of egg size in two marine gastropods: brood order and female size do not contribute to intraspecific variation

Abstract: Egg size has been shown to vary among females in many species of marine invertebrates and fishes. Usually, however, only a single reproductive event is measured for each female, leaving open the possibility that egg size could vary significantly among broods from the same female. Here I measured egg size from 3 to 7 broods per female from 2 calyptraeid species, Crepidula atrasolea and C. ustulatulina, in 2 experiments. In a preliminary experiment, females were raised from hatching under constant temperature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In the two species of Crepidula with planktotrophic development examined in the present study, significant variation in egg size and hatching size was a result of the effects of temperature and maternal identity. Consistent with previous studies of Crepidula with large eggs (Collin, 2010; Collin & Salazar, 2010) and other studies of marine invertebrates (Moran & McAlister, 2009), these two species showed decreased egg size and hatching size with increasing temperature. A large proportion of the observed variation was a result of differences among females (see below).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the two species of Crepidula with planktotrophic development examined in the present study, significant variation in egg size and hatching size was a result of the effects of temperature and maternal identity. Consistent with previous studies of Crepidula with large eggs (Collin, 2010; Collin & Salazar, 2010) and other studies of marine invertebrates (Moran & McAlister, 2009), these two species showed decreased egg size and hatching size with increasing temperature. A large proportion of the observed variation was a result of differences among females (see below).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is not surprising that variation among females is common (e.g. echinoids: Lessios, 1987; Berger & Jelinski, 2008; bivales: Phillips, 2007; gastropods: Collin, 2010). Lessios (1987) found significant differences in egg size between females in each of 13 species of tropical echinoids that were spawned immediately after collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…fornicata , but it has been shown that egg size and energy content may vary with brood order (e.g. [82,83]). Last, temperature might also influence maternal provisioning as has been shown through variations in egg size and hatching size in other calyptraeid species [84].…”
Section: Discussionmentioning
confidence: 99%